Strategische Handelspolitik 2.0 - Thieß Petersen (Wirtschaftsdienst, 2023)
Die Theorie der strategischen Handelspolitik kam in den frühen 1980er Jahren auf. Dabei ging es um die Frage, wie ein Land im Fall von Marktunvollkommenheiten - vor allem oligopolistischen Märkten - den eigenen Wohlstand durch gezielte handelspolitische Maßnahmen steigern kann. Heute gibt es weitere Marktunvollkommenheiten, die ebenfalls den Einsatz handels- und wirtschaftspolitischer Instrumente rechtfertigen. – – The theory of strategic trade policy came into being in the early 1980s. It addressed the question of how a country can increase its own economic welfare through state intervention in the case of oligopolistic world markets. Today, there are many rea-sons that justify government intervention in foreign trade: Cluster risks in importing raw materials and intermediate inputs, different responses to the negative externalities of greenhouse gas emissions, monopolies in the digital economy, and the growing importance of geopolitical considerations. These developments are likely to lead to a renaissance of strategic trade policy interventions, i.e. subsidies, investment controls and trade restrictions, to name only the most important ones.
Keywords: F10; F13; F50; 330; Außenwirtschaftspolitik; Außenwirtschaftspolitik